A faunistic review of the Iranian species of Sphingonotus (Orthoptera, Oedipodinae) with an online key to species - Dey, Lara-Sophie; Saboori, Alireza; Hodjat, Seyed Hossein; Tork, Mahdi; Pahlow, Felix; Husemann, Martin (Zootaxa, 2018)
Sphingonotus is a species-rich genus of band-winged grasshoppers (Oedipodinae), comprising more than 170 species, with its diversity hotspots in the Mediterranean, and in Central and Eastern Asia. Iran represents one of the countries with the highest species diversity for the genus with a total of 31 recorded species. However, no study so far has provided a faunistic overview and no identification keys are available. Here, we present an annotated list of all Sphingonotus species found in Iran derived from records from field observations, museum collections and literature data. Based on morphological and distribution data we synonymize Sphingonotus intutus Saussure, 1888 syn. nov. under Sphingonotus nebulosus persa Saussure, 1884 and Sphingonotus obscuratus transcaspicus Uvarov, 1925 syn. nov. under Sphingonotus obscuratus brunneri Saussure, 1884. We present images of representative specimens (mostly types) of all species, as well as distribution maps and ecological data. Finally, we provide an online key to all known species of Sphingonotus from Iran, which will continuously be updated.